Feminist Paradigm in Qur’anic Exegesis: Integrating Tawhidic Hermeneutics and Qira’ah Mubadalah - Muhammad Zidan Fauzi Al Farisi; Andri Nirwana. AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article formulates an integrative model for interpreting Qur’anic verses on gender relations through Amina Wadud’s tawhidic hermeneutics and Faqihuddin Abdul Kodir’s qira’ah mubadalah. The central question is how tawhid, justice, and reciprocity may become an exegetical procedure that preserves textual authority while preventing patriarchal bias in meaning production. This study employs qualitative library research using descriptive-analytical and thematic-critical analysis of Wadud’s and Kodir’s primary works, selected Qur’anic verses, and contemporary scholarship on gender-sensitive exegesis. The analytical procedure consists of linguistic analysis, socio-historical contextualization, intra-textual coherence, formulation of universal principles, mubadalah-based reciprocity, and maqasid/harm analysis. The application to Q. 9:71, Q. 33:35, and Q. 4:34 demonstrates that the tawhidic–mubadalah integration expands the moral subject of the verses, interprets qiwamah as functional and conditional responsibility, understands nusyuz as a two-way relational problem, and affirms non-violent conflict resolution within family ethics.